ANALISIS TERKAIT PENGENAAN UU PERLINDUNGAN ANAK PADA TINDAK PIDANA PENCABULAN YANG DILAKUKAN OLEH ANGGOTA MILITER : Analysis Related To Imposition Of Child Protection Law On Crimes Of Abuse Committed By Members Of The Military - Alvin Satrya Adhitama Sulistyo; Aprima Suar (Reformasi Hukum Trisakti, 2024)
The criminal act of obscenity can be committed by anyone as stated in decision Number 142-K/PM II-09/AD/IX/2022. The formulation of the problem is whether the perpetrator's actions have met the elements of a criminal act of morality and whether the judge's considerations are in accordance with Law Number 23 of 2014. The research method is normative legal research with a descriptive analytical type, using secondary data then analyzed qualitatively and drawing conclusions deductive. The results of the research and discussion contain elements which in the provisions of Article 281 paragraph (1) of the Criminal Code have been fulfilled, but in this case the judge did not pay enough attention to the fact that one of them was still a minor, so that the actions carried out by the defendant must be subject to the provisions of Article 76E in conjunction with Article 82 paragraph (1) of the Child Protection Law. The conclusion was that the judge's consideration of overriding the principle of "lex specialist derogat lege generali" was not in accordance with Law Number 23 of 2014 because there were victims who were still minors so that the provisions of Article 63 paragraph (2) of the Criminal Code